Pengaruh Status Sosial Ekonomi Orang Tua Terhadap Prestasi Belajar Siswa Kelas IVB SD NO 64/1 Muara Bulian - Budi Purnomo; Ari Rosalina (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2016)
The type of research used in this study is quantitative research, namely research on data collected and expressed in the form of numbers. Based on the analysis, it is known that the social status of parents towards the student achievement of SDN No.64 / 1 Muara Bulian is quite very influential. Furthermore, it has been analyzed based on the coefficient of determinant which states the size of the contribution between variables X and Y Variables is 58.52, which means the socio-economic status of parents contributes 58.52% in creating an influence on student achievement in class IVB SDN No.64 / 1 MuaraBulian. The conclusion taken in this study is that the socio-economic status of parents towards student learning achievement is quite good. Furthermore, the hypothesis test is proposed by comparing the magnitude of r with r which is listed in the table of r product moment values ​​df = N-nr = 25-2 = 23. With df of 25 obtained r at a significant level of α 5% of 0.396. It turns out that r = 0.765 is greater than r = 0.396 at a significant level of α 5%, thus the social status that affects the learning achievement of class IVB SDN No.64 / 1 Muara Bulian.